On the consistency of personality types across adulthood: Latent profile analysis in two large-scale panel studies - Jule Specht; Maike Luhmann; Christian Geiser (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Consistency and change in personality were analyzed by examining personality types across adulthood and old age using data from two nationally representative panel studies from Germany (N = 14,718; 16 - 82 years) and Australia (N = 8,315; 15 - 79 years). In both samples, the Big Five personality traits were measured twice across a period of 4 years. Latent profile analyses and latent profile transition analyses revealed four main findings: First, solutions with 3 (in the German sample) or 4 (in the Australian sample) personality types were found to be most interpretable. Second, measurement invariance tests revealed that these personality types were consistent across all age groups but differed slightly between men and women. Third, age was related to the number of individuals classified within each personality type. Namely, there were more resilients and fewer undercontrollers in older compared with younger age groups. Fourth, there was strong consistency of personality type membership across a period of 4 years in both genders and most age cohorts. Comparatively less consistency across time was found for undercontrollers and individuals in old age. Taken together, these findings show that in the two nations studied here, personality types were highly consistent across gender, age, and time.
Keywords: 330; personality types; adulthood; latent profile analysis; longitudinal study; personality development